NEEDS AND CONCEPT ANALYSIS OF ENVIRONMENTAL MONOGRAPH DEVELOPMENT BASED LOCAL WISDOM IN PROBOLINGGO - Andri Estining Sejati; Sumarmi Sumarmi; I Komang Astina; Singgih Susilo; Putri Tipa Anasi; Fahrudi Ahwan ikhsan; Hendra Hendra; Resti Karmila (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
The problem in the field is that there is a lack of integration between the local wisdom of the Tengger community and environmental conservation efforts in the highland, middle and lowland areas of Probolinggo Regency, so a monograph is needed as a medium for developing learning and preserving culture and the environment. This study aimed to determine the needs and concept analysis for developing an environmental monograph based on local wisdom in the Probolinggo. This study used a qualitative descriptive method. The research subject needs to be analyzed by environmental geography lecturers, students, the Bromo Tengger Semeru National Park Center (BBTNBTS), and the local government of the Probolinggo Regency. The research subjects in the concept analysis were key informants from six villages in the Probolinggo Regency. Qualitative data were obtained through observations, in-depth interviews, and documentation. The data analysis was qualitative, using information from qualitative data to analyze the needs and local wisdom in the upland, middleland, and lowland areas of the Probolinggo. The data analysis was then discussed using the monograph challenge and spatial ethnography. The need for environmental monographs based on local wisdom in the Probolinggo Regency was based on the need to enrich learning resources in the Geography Study Program, State University of Malang, the interests of BBTNBTS, and the Probolinggo Regency Government. The concept that emerged from local wisdom was the preservation of land and forests. Sea and water are sourced from local wisdom in gardening, farming, and fishing.